PENGARUH DEPENDENCY RATIO DAN UMK TERHADAP KESEMPATAN KERJA DAN JUMLAH PENDUDUK MISKIN DI PROVINSI BALI - Ida Ayu Sintya Rahmawati; I Komang Gde Bendesa (E-Jurnal Ekonomi Pembangunan, 2023)
Poverty is still a difficult problem to solve. The Bali Provincial Government has made various efforts to alleviate poverty. However, many other factors also contribute to exacerbating poverty in Bali Province. This study aims to determine how the dependency ratio and UMK affect employment opportunities and poverty in Bali Province. This research uses quantitative research with an associative approach. This study uses secondary data with 108 observations. Secondary data is obtained from the statistical institute of Bali Province. The statistical techniques used are panel data and path analysis. The results of this study show that the dependency ratio and UMK affect employment opportunities and poverty in Bali Province both directly and indirectly.